Analisa Kinerja Jalan Lebak Murni Kecamatan Sako Kota Palembang - Muhammad Agung Tri Putra; Pujiono T; Amelia Rajela (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Jalan Lebak Murni is one of the strategic connecting roads in Palembang City, playing a vital role in supporting the mobility of the community and ensuring the smooth distribution of goods and services across regions. In recent years, the area surrounding this road has experienced rapid development, particularly in the residential sector, which has led to a significant increase in traffic volume. This condition has contributed to a decline in the road’s performance. This study aims to analyze the existing condition of Jalan Lebak Murni, assess the level of pavement damage, and formulate technical recommendations to improve the quality of road infrastructure in a sustainable manner. The methodology includes a visual survey of pavement conditions, daily traffic data collection to determine vehicle load characteristics, and geometric road analysis based on technical standards set by the Directorate General of Highways (Direktorat Jenderal Bina Marga). The study findings indicate that the surge in vehicle volume, especially four-wheeled motor vehicles and heavy vehicles, is one of the main contributing factors. Therefore, technical actions such as increasing road capacity and reconfiguring geometric elements are required to ensure optimal road service function. The resulting technical recommendations are expected to serve as a foundation for more effective and sustainable road development and maintenance planning.